Meaning of work and disability: a study with chairmen after spinal injury (Gestão & Regionalidade, 2024)
People who have acquired a physical disability tend to be more prone to the need for work. In this context, the general objective of this study is to understand the meanings built on work for wheelchair users with acquired disabilities. A qualitative research was carried out in which seven subjects were interviewed in depth in this profile. The interviews were transcribed and analyzed through content analysis. The meanings related to work were grouped into: guarantee of security, independence and autonomy; source of satisfaction; efficiency and driving results; maintenance of occupation and feeling of usefulness; building positive social relationships; morally acceptable and social contribution; occupation of spaces and social representativeness; denial of the stigma of disability and effective inclusion. It was concluded that the meanings of work for wheelchair users are anchored, not only in the instrumental character, but also in the issues of space occupation, social utility and breaking of capacitism.